The Relationship between the Economic and Financial Crises and Unemployment Rate in the European Union: How Institutions Affected Their Linkage? - Ionuț Jianu (Journal of Eastern Europe Research in Business and Economics, 2019)
This paper aims to estimate the impact of economic and financial crises on the unemployment rate in the European Union, taking also into consideration the institutional specificities, since unemployment was the main channel through which the economic and financial crisis influenced the social developments.. In this context, I performed two institutional clusters depending on their inclusive or extractive institutional features and, in each cases, I computed the crisis effect on unemployment rate over the 2003-2017 period. Both models were estimated by using Panel Estimated Generalized Least Squares method, and are weighted by Period SUR option in order to remove, in advance the possible inconveniences of the models. The institutions proved to be a relevant criterion that drives the impact of economic and financial crises on the unemployment rate, highlighting that countries with inclusive institutions are less vulnerable to economic shocks and are more resilient than countries with extractive institutions. The quality of institutions was also found to have a significant effect on the response of unemployment rate to the dynamic of its drivers.
Keywords: C23; E24; G01; 330; unemployment; financial shocks; crisis; dummy; youth